Within- and between-mesocycle variations of well-being measures in top elite soccer players: a longitudinal study - Oliveira, Rafael (2021)
The aim of this study was two-fold: (a) to describe the in-season variations of training monotony (TM), training strain (TS), and acute: chronic workload ratio (ACWR) through fatigue, stress, muscle soreness and sleep quality; (b) to compare those variations between player status and player positions. Seventeen professional players from an European First League team participated in this study. Regarding player status, participants were divided in two groups: starters (n=9), and non-starters (n=8). Additionally, they were divided according to player positions: four central defenders, three wide defenders, four central midfielders, three wide midfielders, and three strikers. They were monitored daily over a 40-week period of competition through the Hooper index. Then, TM, TS, and ACWR were calculated for each Hooper index categories, respectively. Data were analysed across ten mesocycles (M: 1 to 10). Results revealed variations over the season with respect for both player status and positions. There was a tendency of higher values for all TM, TS, and ACWR calculated from Hooper categories, for starters compared to non-starters. Regarding player positions, there were variations over the season but only significant differences in stress between wide defenders vs central midfielders for monotony (p=0.033, ES=5.16) and central defenders vs wide defenders for ACWR (p=0.044, ES=4.95), and in sleep between wide defenders and strikers for TM (p=0.015, ES= 5.80). The present study showed that a comprehensive analysis of players' wellness parameters can provide clear information to the coaches tp complement training monitoring of the players.